The level of viability of milkfish (Chanos chanos) in transportation containers with different temperatures - Fendi; Sarfiani; Karyawati; Rochmady; Abdul Rakhfid (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2018)
The transportation of milkfish (Chanos chanos) is an important factor determining the survival of milkfish (Chanos chanos). The hatchery is not always close to the location of the aquaculture pond, so the treatment in transportation using land and sea vehicles to arrive at the aquaculture site/pond. This study aims to determine the effect of different temperatures in milkfish (Chanos chanos) transportation to obtain a good temperature in milkfish (Chanos chanos) transportation. The research method uses a completely randomized design (CRD) with three treatments and three replications. The treatments given were treatment A (temperature 15oC), treatment B (temperature 18oC), and treatment C (temperature 21oC). While the time taken for each treatment is 14 hours. The results showed that the survival of milkfish (Chanos chanos) were in the range of 90.04% (treatment A), 95.04% (treatment B), and 88.67% (treatment C), where the highest survival in treatment B is 95.04%.